2014
DOI: 10.1371/journal.pone.0103848
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Molecular Markers, Pfmdr1-N86Y and Pfcrt-K76T, with In Vitro Chloroquine Resistant Plasmodium falciparum, Isolated in the Malaria Endemic States of Assam and Arunachal Pradesh, Northeast India

Abstract: The mechanism of chloroquine (CQ) resistance in Plasmodium falciparum is not clearly understood. However, CQ resistance has been shown to be associated with point mutations in Pfcrt and Pfmdr1. These genes encode for digestive vacuole transmembrane proteins Pfcrt and Pgh1, respectively. The present study was carried out to analyze the association of Pfcrt-K76T and Pfmdr1-N86Y mutations with CQ resistance in Northeast Indian P. falciparum isolates. 115 P. falciparum isolates were subjected to in vitro CQ sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Parasites isolated in untreated infections can harbour resistant genes as a tool for survival; this study reports the presence of Pfmdr1 86Y (confirmed by sequencing) and 1246Y mutant alleles being transmitted in asymptomatic as well as symptomatic infections. This finding is similar to reports from endemic and non-endemic areas where Pfmdr1 has served as a molecular marker of detecting anti-malarial drug resistance [13, 14, 16, 21]. Most malaria-endemic countries are in the pre-elimination phase because local transmission is still high [2].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Parasites isolated in untreated infections can harbour resistant genes as a tool for survival; this study reports the presence of Pfmdr1 86Y (confirmed by sequencing) and 1246Y mutant alleles being transmitted in asymptomatic as well as symptomatic infections. This finding is similar to reports from endemic and non-endemic areas where Pfmdr1 has served as a molecular marker of detecting anti-malarial drug resistance [13, 14, 16, 21]. Most malaria-endemic countries are in the pre-elimination phase because local transmission is still high [2].…”
Section: Discussionsupporting
confidence: 85%
“…Although this study did not assess Pfcrt mutation, there is known synergy between mutations on Pfmdr1 and Pfcrt genes [39]. Studies in Nigeria and other areas have reported reduced in vitro and in vivo response in chloroquine-resistant isolates bearing the 76T mutation correlating strongly with Pfmdr1 86Y mutation [12, 14, 16, 21, 22, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study population, there was no association of N86Y mutation of the pfmdr1 gene with CQ resistance and this non-association was in agreement with previous findings [16] , [20] , [25] , [26] . However, the prevalence of N86Y mutation was high in other Indian P. falciparum isolates [16] , [27] , [28] .…”
Section: Discussionmentioning
confidence: 83%
“…Initial denaturation at 94°C for 10 minutes followed by 40 cycles of denaturation at 94°C for 1 minute, annealing at 56°C for 1 min, and extension at 72°C for 1 min 30 seconds [32].…”
Section: Pfcrt-omentioning
confidence: 99%